Oil Price Volatility, Economic Growth and the Hedging Role of Renewable Energy - Rentschler, Jun E. (World Bank, Washington, DC, 2013)
This paper investigates the adverse effects of oil price volatility on economic activity and the extent to which countries can hedge against such effects by using renewable energy. By considering the Realized Volatility of oil prices, rather than following the standard approach of considering oil price shocks in levels, the effects of factor price uncertainty on economic activity are analyzed. Sample countries represent developed and developing, oil importing and exporting and service/industry-based economies (United States, Japan, Germany, South Korea, India, and Malaysia) and thus complement the standard literature's analysis of Western OECD countries. In a vector auto-regressive setting, Granger causality tests, impulse response functions, and variance decompositions show that oil price volatility has more-adverse effects in all sample countries than oil price shocks alone can explain. The paper finds that the sensitivity to oil price volatility varies widely across countries and discusses various factors which may determine the level of sensitivity (such as sectoral composition and the energy mix). This implies that the standard approach of solely considering net oil importer-exporter status is not sufficient. Simulations of volatility shocks in hypothetical energy mixes (with increased renewable shares) illustrate the potential economic benefits resulting from efforts to disconnect the macroeconomy from volatile commodity markets. It is concluded that expanding renewable energy can in principle reduce an economy's vulnerability to oil price volatility, but a country-specific analysis would be necessary to identify concrete policy measures. Overall, the paper provides an additional rationale for reducing exposure and vulnerability to oil price volatility for the sake of economic growth.